Second Year Winner: Pawmi: An Exploration of Rhetoric in Pokémon Relevance: PRWR 2007, Rhetoric: Strategy and Application. CD: Laura Allen. - MacIsaac, Robert (Noteworthy: The LA&PS Writing Prizes, 2023)
In this interesting paper, the author effectively explores the rhetorical similarities and differences within Pokémon’s generational mascots. Pokémon, an intellectual property featuring video games, anime and trading cards, features a series of fantastic creatures (Pokémon) who gain levels (and thus power/new abilities) through completing quests or player vs. player combat. The generational mascots represent each new iteration of the game, and so are designed to look visually similar through their various incarnations—instantly recognizable as Pokémon to a wide group of fans even if the particulars differ from year to year. The author carefully explores the design elements of “Pawmi,” the 9th Generation mascot, and argues that the mascots are ongoing a slow evolution, which finds its most recent apotheosis in shifts to Pawmi’s design. The writer, making use of course concepts and a fine, accessible writing style, recognizing how minor changes to Pawmi have allowed for a shift in branding from “cute” to “strong and powerful”—but without abandoning the charming and appealing elements of previous designs. This analysis demonstrates how the Pokémon brand has managed to retain traditional elements of rhetorical communication via design, but still update their mascot for a modern audience. Convincing and usefully illustrated, this rhetorical analysis is very effective indeed at deconstructing an iconic popular brand.